(untitled) (Fiep Bulletin - online, 2013)
In the article author’s present results of long-term research aimed at the maximal running speed development with use of the supra-maximal speed means. They succeeded to establish the optimal pulling force (20 – 40 N) that enables to reach 105 – 108 % of the maximal running speed. In this speed the kinematical parameters between maximal and supra-maximal speed do not differ considerably and this secures their optimal transfer into competition activity. Authors proved that there can be different effects on sprinters according stimulus magnitude of supra-maximal speed, but also according individual specialities of adaptation sprinters’ reaction.